Soldering paste, ceramic copper-clad plate and method for preparing ceramic copper-clad plate

By using metal compound solder paste with high conductivity to form ceramic copper clad plates on the surface of the ceramic matrix, the problems of poor conductivity and large thermal resistance of the ceramic copper clad plates are solved, and their reliability and peel strength are improved.

CN119820169APending Publication Date: 2025-04-15BYD CO LTD +1

Patent Information

Application Number
CN202411998474.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-31
Publication Date
2025-04-15

AI Technical Summary

Technical Problem

The current ceramic copper clad plate has poor conductivity, resulting in large thermal resistance and poor proportion of solder layer components, resulting in low cyclic thermal stress resistance and low peel strength.

Method used

A solder paste including a metal compound of a core layer, a first shell layer and a second shell layer, the conductivity of the core layer is greater than or equal to 80% IACS, and solder paste is provided on the surface of the ceramic substrate by screen printing, and brazing is performed to form a ceramic copper clad plate.

Benefits of technology

The electrical conductivity of the ceramic copper clad plate is improved, thermal resistance is reduced, dense solder layer is formed, void is reduced, and reliability and peel strength are improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119820169A_ABST
    Figure CN119820169A_ABST
Patent Text Reader

Abstract

The invention relates to soldering paste, a ceramic copper-clad plate and a method for preparing the ceramic copper-clad plate, and the soldering paste comprises a metal compound which comprises a core layer, a first shell layer and a second shell layer, the first shell layer wraps the core layer, and the second shell layer wraps the first shell layer; the core layer has a conductivity greater than or equal to 80% IACS. According to the scheme provided by the invention, the conductivity of the ceramic copper-clad plate can be improved, the thermal resistance can be reduced, a compact welding layer can be formed on the ceramic copper-clad plate, holes can be reduced, and the reliability and peel strength of the ceramic copper-clad plate are improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of power electronics technology, and in particular to a solder paste, a ceramic copper clad laminate, and a method for preparing the ceramic copper clad laminate. Background Art

[0002] Ceramic copper clad laminate has the advantages of high strength, good chemical stability and high thermal conductivity. It is an ideal matrix material for power devices. It can provide physical support for chips, connect circuits, and form heat dissipation channels.

[0003] In the related technology, the current ceramic copper clad laminate has poor conductivity, which will lead to a large thermal resistance of the ceramic copper clad laminate; secondly, the proportion of each component in the solder layer of the ceramic copper clad laminate is not good, resulting in low cyclic thermal stress tolerance of the ceramic copper clad laminate, which makes the peel strength of the ceramic copper clad laminate low.

[0004] Therefore, the current solder paste, method for preparing ceramic copper clad laminate and ceramic copper clad laminate still need to be improved. Summary of the invention

[0005] In order to solve or partially solve the problems existing in the related art, the present application provides a solder paste, a ceramic copper clad laminate and a method for preparing a ceramic copper clad laminate, which can improve the conductivity of the ceramic copper clad laminate, reduce thermal resistance, and form a dense solder layer on the ceramic copper clad laminate, which can reduce voids and improve the reliability and peel strength of the ceramic copper clad laminate.

[0006] In a first aspect, the present application provides a solder paste comprising a metal compound, wherein the metal compound comprises a core layer, a first shell layer and a second shell layer, wherein the first shell layer wraps the core layer and the second shell layer wraps the first shell layer; and the conductivity of the core layer is greater than or equal to 80% IACS.

[0007] In combination with the first aspect, in a possible implementation of the first aspect, the thickness ratio of the core layer, the first shell layer, and the second shell layer is (2-15): (1-9): (0.5-5).

[0008] In combination with the first aspect, in a possible implementation of the first aspect, a binder is also included, wherein the binder includes 75-98wt% of a solvent, 0.1-20wt% of a dispersant, 0.05-15wt% of a thickener, 0.05-0.1wt% of a surfactant and 0.01-10wt% of a thixotropic agent.

[0009] In combination with the first aspect, in a possible implementation of the first aspect, the solvent includes one or more of pineol, tributyl citrate, diethylene glycol butyl ether and diethylene glycol butyl ether acetate; and / or the dispersant includes one or more of DISPERBYK-168, stearic acid, polyethylene glycol 200 and polyethylene glycol 400; and / or the thickener includes one or more of ethyl cellulose, polyvinyl alcohol and acrylic resin; and / or the surfactant includes one or more of Tween 20, a silicon-based coupling agent and sodium dodecylbenzene sulfonate; and / or the thixotropic agent includes one or more of polyamide wax, modified polyurea and hydrogenated castor oil.

[0010] In combination with the first aspect, in a possible implementation of the first aspect, the mass fraction of the metal compound in the solder paste is 70-95wt%, and the mass fraction of the binder is 5-30wt%; the particle size range of the solder paste is 0.5um-50um, and the viscosity range of the solder paste is 20Pas-300Pas.

[0011] A second aspect of the present application provides a ceramic copper clad laminate, comprising: a solder layer made of the solder paste as described above.

[0012] In combination with the second aspect, in a possible implementation of the second aspect, the welding layer includes a TiN layer and a transition alloy layer, and the thickness ratio of the TiN layer and the transition alloy layer in the welding layer is (0.05-0.1): (0.9-0.95).

[0013] In combination with the second aspect, in a possible implementation manner of the second aspect, the thickness of the TiN layer is 0.05 μm-5 μm, and the thickness of the transition alloying layer is 2.95 μm-10 μm.

[0014] In combination with the second aspect, in a possible implementation manner of the second aspect, the transition alloying layer includes a discontinuous intermetallic compound layer and a copper-based solid solution layer.

[0015] In combination with the second aspect, in a possible implementation of the second aspect, an area ratio of the discontinuous intermetallic compound layer and the copper-based solid solution layer in the transition alloying layer is (0.3-0.5):(0.5-0.7).

[0016] In combination with the second aspect, in a possible implementation manner of the second aspect, the discontinuous intermetallic compound layer consists of TiSi and TiCu.

[0017] In combination with the second aspect, in a possible implementation manner of the second aspect, it further includes a ceramic substrate, and the thickness of the ceramic substrate is 0.2-2 mm.

[0018] The third aspect of the present application provides a method for preparing a ceramic copper-clad laminate, comprising providing a ceramic substrate; arranging solder paste on both side surfaces of the ceramic substrate to generate solder layers on both side surfaces of the ceramic substrate, wherein the solder paste is the solder paste described above; arranging a copper sheet on the side surface of the solder paste away from the ceramic substrate, and performing a brazing process to obtain the ceramic copper-clad laminate.

[0019] In combination with the third aspect, in a possible implementation of the third aspect, the process of setting the solder paste includes screen printing, the screen printing thickness of the screen printing is 6um-20um, the thickness of the solder layer is 3-15um, the brazing treatment includes vacuum brazing treatment, the temperature of the vacuum brazing treatment is 850-1060°C, and the time of the vacuum brazing treatment is 10min-120min.

[0020] The technical solution provided by this application may have the following beneficial effects:

[0021] The solder paste, ceramic copper-clad laminate and method for preparing the ceramic copper-clad laminate of the present application include a metal compound, wherein the metal compound includes a core layer, a first shell layer and a second shell layer, wherein the first shell layer wraps the core layer and the second shell layer wraps the first shell layer; the conductivity of the core layer is greater than or equal to 80% IACS, which can improve the conductivity of the ceramic copper-clad laminate, reduce thermal resistance, and form a dense solder layer on the ceramic copper-clad laminate, thereby reducing voids and improving the reliability and peel strength of the ceramic copper-clad laminate.

[0022] It should be understood that the foregoing general description and the following detailed description are exemplary and explanatory only and are not restrictive of the present application. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] The above and other objects, features and advantages of the present application will become more apparent by describing in more detail exemplary embodiments of the present application in conjunction with the accompanying drawings, wherein the same reference numerals generally represent the same components in the exemplary embodiments of the present application.

[0024] Figure 1 It is a schematic diagram of a process for preparing a ceramic copper-clad laminate shown in an embodiment of the present application;

[0025] Figure 2 is a schematic diagram of the structure of the metal compound shown in the embodiment of the present application;

[0026] Figure 3 It is a schematic diagram of the structure of the welding layer of the ceramic copper clad laminate shown in the embodiment of the present application. DETAILED DESCRIPTION

[0027] The embodiments of the present application will be described in more detail below with reference to the accompanying drawings. Although the embodiments of the present application are shown in the accompanying drawings, it should be understood that the present application can be implemented in various forms and should not be limited by the embodiments described herein. On the contrary, these embodiments are provided to make the present application more thorough and complete, and to fully convey the scope of the present application to those skilled in the art.

[0028] The terms used in this application are for the purpose of describing specific embodiments only and are not intended to limit this application. The singular forms of "a", "an" and "the" used in this application and the appended claims are also intended to include plural forms unless the context clearly indicates other meanings. It should also be understood that the term "and / or" used herein refers to and includes any or all possible combinations of one or more associated listed items.

[0029] It should be understood that although the terms "first", "second", "third", etc. may be used in this application to describe various information, this information should not be limited to these terms. These terms are only used to distinguish the same type of information from each other. For example, without departing from the scope of this application, the first information may also be referred to as the second information, and similarly, the second information may also be referred to as the first information. Thus, the features defined as "first" and "second" may explicitly or implicitly include one or more of the features. In the description of this application, the meaning of "multiple" is two or more, unless otherwise clearly and specifically defined.

[0030] In related technologies, semiconductor power devices are constantly developing towards high power, miniaturization, integration and multi-function, which has accelerated the iterative upgrade of chip heat dissipation substrate performance. Ceramic copper clad laminates have excellent electrical and insulating properties and are widely used as chip heat dissipation substrates in the field of power electronics packaging power semiconductor components. Ceramic copper clad laminates prepared by active metal brazing (AMB) are new products that improve the bonding performance and reliability of traditional direct copper clad (DBC) copper clad laminates. Commonly used ceramics include AlN, Si 3 N 4 、Al 2 O 3 , ZTA, etc., mainly use solder containing active elements to join ceramics and metals together by brazing. The ultrasonic yield and performance are better than the direct copper plating process.

[0031] The industry's copper-clad aluminum substrates mostly use the DBC process, which has the characteristics of low ultrasonic yield (about 90%) and poor reliability. The aluminum-clad aluminum substrates prepared by the AMB process are prone to broken boards due to differences in the content and distribution of active elements, and black etching due to differences in the zirconium oxide content in ZTA ceramics. These problems limit the development and commercial use of copper-clad aluminum substrates with high yield and reliability. The copper-clad boards made by the traditional DBC process have a single interface component, high brittleness, and low tolerance to cold and heat; technical processes such as atmospheric plasma spraying are inefficient, and it takes time to spray to the required metal layer thickness, which is not convenient for mass production and has high indirect costs; the oxygen content of raw materials is strictly required, and the current carrying capacity and heat dissipation capacity are low, not as good as oxygen-free pure copper.

[0032] However, ceramic copper clad laminates made using relevant process technologies have multiple disadvantages. When copper-based solders mainly composed of Cu, Sn, and Ti are used to manufacture the solder layer, the titanium content is low and the tin content is high and difficult to control, which affects the thermal conductivity of the ceramic copper clad laminate. In addition, the intermetallic phase in the solder layer of the current ceramic copper clad laminate accounts for a large proportion and the lattice mismatch at the dispersed heterogeneous interface reduces the thermal conductivity of the solder layer, resulting in a large thermal resistance of the ceramic copper clad laminate, and the proportion of each component in the solder layer is not good, resulting in a low tolerance to cyclic thermal stress of the ceramic copper clad laminate, which makes the peel strength of the ceramic copper clad laminate low.

[0033] In response to the above problems, the embodiments of the present application provide a solder paste, a ceramic copper clad laminate and a method for preparing a ceramic copper clad laminate, which can improve the conductivity of the ceramic copper clad laminate, reduce thermal resistance, and form a dense solder layer on the ceramic copper clad laminate, thereby reducing voids and improving reliability and peel strength.

[0034] The technical solution of the embodiments of the present application is described in detail below with reference to the accompanying drawings.

[0035] In one aspect of the present application, a solder paste is proposed, comprising a metal compound, wherein the metal compound comprises a core layer, a first shell layer and a second shell layer, wherein the first shell layer wraps the core layer and the second shell layer wraps the first shell layer; the conductivity of the core layer is greater than or equal to 80% IACS.

[0036] from Figure 2It can be seen that, specifically, the core layer can be a high-conductivity copper alloy powder, such as CuPAg, CuBiTe, etc., the conductivity of the core layer is ≥80% IACS, and the preferred conductivity is ≥85% IACS. The solder layer in the ceramic copper-clad laminate of the related art will have more intermetallic phases occupying a large proportion of the solder layer, resulting in weak conductivity of the ceramic copper-clad laminate, and the conductivity of the core layer is ≥80% IACS. After the solder layer is generated on the ceramic copper-clad laminate, the distribution ratio of the intermetallic phase such as TiSn and CuSn in the solder layer can be reduced, which can improve the conductivity of the ceramic copper-clad laminate and reduce the thermal resistance of the ceramic copper-clad laminate. Furthermore, the core layer can also be a high-conductivity copper-based composite material, a high-conductivity aluminum-based composite material, diamond, WC and other powder particles; the first shell layer can be a low-melting point alloy such as SnCu, SnSb, CuSnP, GaInSn, etc., and the second shell layer can be an alloy containing active elements, such as hydrides, metal salts, intermediate alloys, such as TiH 2 , TiSn, CuTi, etc. The low melting point alloy powder in the first shell layer wets the core layer alloy powder and the copper layer, and is the alloy liquid required for the uniform flow of the active element alloy in the second shell layer. It can promote the wetting metallurgical chemical reaction between the active elements and the ceramic, core layer alloy, and copper layer to form a dense solder layer, so that the ceramic copper clad laminate has a lower void distribution.

[0037] In one possible embodiment, the thickness ratio of the core layer, the first shell layer and the second shell layer is (2-15):(1-9):(0.5-5), for example, the thickness ratio of the core layer, the first shell layer and the second shell layer is 2:5:0.5; preferably, the thickness ratio of the core layer, the first shell layer and the second shell layer is (3-10):(4-8):(1-3), for example, the thickness ratio of the core layer, the first shell layer and the second shell layer is 3:6:1; more preferably, the thickness ratio of the core layer, the first shell layer and the second shell layer is (6-9):(4-5):(1-2), for example, the thickness ratio of the core layer, the first shell layer and the second shell layer is 6:4:1, and the core layer has a larger thickness value than the first shell layer and the second shell layer, which can improve the conductivity of the ceramic copper clad laminate. According to the different thickness ratios of the core layer, the first shell layer and the second shell layer in the solder paste, the plasticity and hardness of the solder layer can be improved, and the tolerance of the ceramic copper clad laminate to cyclic thermal stress can be improved.

[0038] In a possible implementation, a binder is further included, and the binder includes 75-98wt% of a solvent, 0.1-20wt% of a dispersant, 0.05-15wt% of a thickener, 0.05-0.1wt% of a surfactant and 0.01-10wt% of a thixotropic agent.

[0039] Specifically, the adhesive can be made by mixing a solvent, a surfactant, a dispersant, a thickener, and a thixotropic agent according to a certain proportion. Specifically, the adhesive in the solder paste can be made by mixing the solvent, the surfactant, the dispersant, the thickener, and the thixotropic agent by heating in an electromagnetic water bath, stirring, mixing, and filtering. The adhesive includes 75-98wt% of a solvent, preferably 80%-95% of a solvent, and more preferably 85%-95% of a solvent; 0.1-20wt% of a dispersant, preferably 1-15% of a dispersant, and more preferably 2.5-10% of a dispersant; 0. 0.5-15wt% thickener, preferably 1-10% thickener, more preferably 1.5-5% thickener; 0.05-0.1wt% surfactant, preferably 0.1-0.5% surfactant, more preferably 0.3-0.5% surfactant; 0.01-10wt% thixotropic agent, preferably 0.1-5% thixotropic agent, more preferably 0.5-3% thixotropic agent. The binders composed of different proportions can better combine with the metal compound, make the solder paste more suitable when used, and increase the shelf life of the solder paste.

[0040] In this application, all the numbers disclosed herein are approximate values, regardless of whether the words "about" or "approximately" are used. The value of each number may vary by less than 10% or a reasonable difference considered by those skilled in the art, such as 1%, 2%, 3%, 4% or 5%.

[0041] In one possible embodiment, the solvent includes one or more of pineol, tributyl citrate, diethylene glycol butyl ether and diethylene glycol butyl ether acetate; and / or the dispersant includes one or more of DISPERBYK-168, stearic acid, polyethylene glycol 200 and polyethylene glycol 400; and / or the thickener includes one or more of ethyl cellulose, polyvinyl alcohol and acrylic resin; and / or the surfactant includes one or more of Tween 20, a silicon-based coupling agent and sodium dodecylbenzene sulfonate; and / or the thixotropic agent includes one or more of polyamide wax, modified polyurea and hydrogenated castor oil.

[0042] In a possible implementation manner, the mass fraction of the metal compound in the solder paste is 70-95wt%, preferably, the mass fraction of the metal compound in the solder paste is 80-88wt%, the mass fraction of the binder is 5-30wt%, preferably, the mass fraction of the binder is 12-20wt%. The particle size range of the solder paste is 0.5um-50um, preferably the particle size range is 0.8um-25um, the viscosity range of the solder paste is 20Pas-300Pas, preferably the viscosity range is 40Pas-150Pas, the appropriate particle size distribution and viscosity range of the solder paste can help improve the compactness of the screen printing area, and facilitate the volatilization and exhaust of the organic carrier, the screen printing thickness can affect the thickness of the final solder layer, and ultimately improve the reliability of the ceramic copper clad laminate.

[0043] The solder paste of the present application includes a metal compound, which includes a core layer, a first shell layer and a second shell layer, wherein the first shell layer wraps the core layer and the second shell layer wraps the first shell layer; the conductivity of the core layer is greater than or equal to 80% IACS, which can improve the conductivity of the ceramic copper clad laminate, reduce thermal resistance, and form a dense solder layer on the ceramic copper clad laminate, which can reduce voids and improve reliability and peel strength.

[0044] In another aspect of the present application, the present application proposes a method for preparing a ceramic copper-clad laminate, comprising: providing a ceramic substrate; placing solder paste on both sides of the ceramic substrate, and forming solder layers on both sides of the ceramic substrate; placing a copper sheet on the side of the solder paste away from the ceramic substrate, and performing a brazing process to obtain a ceramic copper-clad laminate. Thus, good welding between the ceramic substrate and the copper layer can be achieved, and a ceramic copper-clad laminate with excellent performance can be obtained.

[0045] In a possible implementation manner, the solder layer includes a TiN layer and a transition alloy layer, and the thickness ratio of the TiN layer to the transition alloy layer in the solder layer is (0.05-0.1):(0.9-0.95).

[0046] In a possible implementation manner, the thickness of the TiN layer is 0.05 μm-5 μm, and the thickness of the transition alloy layer is 2.95 μm-10 μm.

[0047] In one possible implementation, the transition alloying layer includes a discontinuous intermetallic compound layer and a copper-based solid solution layer.

[0048] In a possible implementation manner, the area ratio of the discontinuous intermetallic compound layer and the copper-based solid solution layer in the transition alloying layer is (0.3-0.5):(0.5-0.7).

[0049] In one possible implementation, the discontinuous intermetallic compound layer consists of TiSi and TiCu.

[0050] In a possible implementation manner, the thickness of the ceramic substrate is 0.2-2 mm, and the thickness of the copper sheet is 0.1 mm-5 mm.

[0051] Specifically, see Figure 1 , the method for preparing a ceramic copper clad laminate may include the following steps:

[0052] S100: providing a ceramic substrate.

[0053] According to some embodiments of the present application, a ceramic substrate is provided in this step, and the type of the ceramic substrate is not particularly limited. For example, the ceramic substrate may include ceramic materials such as aluminum nitride, aluminum oxide, silicon carbide, and zirconium oxide ceramics.

[0054] According to some embodiments of the present application, the metal compound in the solder paste can be prepared by the following method:

[0055] 1) Place alloy powder with conductivity ≥ 80% IACS in a ball mill according to specific gravity, add a process control agent, and perform ball milling for 15 minutes at a speed of 60-150 rpm. The ball milling environment can be vacuum, argon, or nitrogen.

[0056] 2) Then, the low melting point alloy powder is placed in a ball mill according to its specific gravity, and a process control agent is added. The ball mill is firstly performed at 150 rpm for 15 minutes, and then the speed is increased to 1000 rpm. The ball mill is performed for 6-8 hours each time, and the cooling water temperature is 20-35°C. After the ball milling, the temperature is slowly lowered to room temperature, and a vibrating screening machine is used to screen out agglomerated particles, and the intermediate alloy powder is placed in a box for storage.

[0057] 3) Put active metal Ti or titanium hydride into a ball mill, and put a certain amount of process control agent, first at 150rpm, after ball milling for 15min, put the intermediate alloy powder prepared in step 2) and a certain amount of process control agent, and then after ball milling at 150rpm for 15min, continue to ball mill at 500rpm-800rpm for 3-48 hours. When the ball milling slowly drops to room temperature, use a vibrating screen to screen out metal compounds of suitable particle size. The uniform ball milling speed is preferably 500rpm-700rpm, and the ball milling time is preferably 3-8h. The process control agent can be one or a mixture of stearic acid, oleic acid, chitosan, and PEG, preferably stearic acid and chitosan, and the addition amount is 1-30% of the weight of the metal compound, preferably 3-25%, and more preferably 5-20%.

[0058] The binder can be prepared by the following method: first, nitrogen is introduced into the reactor, and the introduction is repeated three times to exhaust the air in the reactor; then the solvent is added into the reactor through a glass pipe, and the temperature is slowly raised to 60°C-120°C while stirring at a low speed of 30-100 rpm; then the thickener is slowly introduced into the solvent through the pipe, and stirred at a low speed of 50-150 rpm for 30-120 minutes, and then stirred at 120-600 rpm for 30-90 minutes; then the dispersant and the surfactant are simultaneously added into the reactor. Add to the above solution, stir at 80-150rpm, generally heat to 150-250℃, and stir for 1h-5h; after cooling, filter with 100-500 mesh gauze, use viscometer to test viscosity, and adjust the ratio of thixotropic agent to solvent according to the required viscosity, then stir slowly at a low speed of 30-80rpm, after the temperature rises to 45-80℃, adjust the speed to 800-1500rpm, stir for 1h-5h, and finally filter with 200-500 mesh gauze to obtain the adhesive.

[0059] After obtaining the binder, the metal compound and the binder are mixed in a certain proportion, and a vacuum planetary disperser is used to mix and stir, and then filtered evenly. Specifically, the powdered metal compound and the binder are first stirred and mixed, with a stirring speed of 30-60RPM, a dispersion speed of 100-300rpm, and a stirring time of 0.5-3h; then uniform stirring is performed, with a stirring speed of 300-800RPM and a stirring time of 1-3h; finally, vacuum stirring is performed, with a speed of 500-1200RPM, a stirring time of 1-3h, and a vacuum degree of -99KPa. After observing that there are no bubbles on the surface of the solder paste and it is in a uniform and smooth flow state, the material is collected to obtain the solder paste. Through this stirring method, stirring at a low speed can make the binder fully infiltrate the powdered metal compound, avoiding excessive heat generated by mixing at a high speed, which causes excessive volatilization of the binder.

[0060] S200: Solder paste is provided on the surface of the ceramic substrate.

[0061] According to some embodiments of the present application, in this step, solder paste is provided and disposed on the surface of the ceramic substrate. Specifically, providing the solder paste may include: providing a binder; dispersing a powdered metal compound in the binder to obtain the solder paste. For example, the components of the binder may be uniformly mixed to form a viscous liquid, and then the powdered metal compound may be uniformly dispersed in the viscous liquid by mechanical stirring or the like.

[0062] According to some embodiments of the present application, the process of setting the solder paste is not particularly limited. For example, the process of setting the solder paste may include screen printing, and the solder paste may be set on the surface of the ceramic substrate. The screen printing thickness is 6-20um, preferably 8-20um, and more preferably 8-19um.

[0063] S300: a copper layer is provided on the surface of the solder paste on the side away from the ceramic substrate.

[0064] According to some embodiments of the present application, in this step, a copper layer is arranged on the surface of the side of the solder paste away from the ceramic substrate, and the type of the copper layer is not particularly limited. For example, the copper layer can be a copper sheet, and the thickness of the copper sheet can be 0.1mm-5mm, preferably 0.25mm-1mm, and more preferably 0.3-0.9mm. The copper purity can be 99.96%, preferably 99.99%. The ratio of the copper layer thickness on both sides of the ceramic substrate can be 0.2-1, preferably 0.5-1, and more preferably 0.6-0.8. The thickness of the ceramic substrate can be 0.2-2mm, preferably 0.25-1.2mm, and more preferably 0.25-0.6mm.

[0065] S400: Brazing process is performed to obtain a ceramic copper clad laminate.

[0066] According to some embodiments of the present application, in this step, the solder paste is brazed to obtain a ceramic copper-clad laminate. The brazing process is not particularly limited. For example, when a copper sheet is used as the copper layer, the brazing process may be a vacuum brazing process, wherein the temperature of the vacuum brazing process may be 850-1060°C, preferably 880-980°C, more preferably 900-960°C, and the vacuum degree may be 10 -2 -10 -5 Pa, preferably 10 -2 -10 -4 Pa, more preferably 10 -2 -10 -3 Pa, the vacuum brazing treatment time can be 30-180min, preferably 45-75min, the heat preservation time can be 10min-120min, preferably 20min-60min, more preferably 45-55min; the difference between the heating rate and the cooling rate is ≤15℃ / min, preferably ≤10℃ / min, more preferably ≤3℃ / min, and the pressure weight can be 5N-360N, preferably 7N-120N, more preferably 19-30N; in addition to the vacuum brazing treatment, inert gas can also be used, such as nitrogen, argon, hydrogen, vacuum + nitrogen / argon / hydrogen and other combinations, and the gas purity is preferably 99.999%. The brazing treatment using the vacuum brazing process can prevent the metal elements in the metal compound and the copper sheet from being oxidized.

[0067] In another aspect of the present application, the present application provides a ceramic copper clad laminate prepared by the aforementioned method. Therefore, the ceramic copper clad laminate has all the features and advantages of the aforementioned method, which will not be described in detail here.

[0068] According to some embodiments of the present application, the thermal resistance of the ceramic copper clad laminate is ≤0.09℃*cm^2 / W, preferably, ≤0.085℃*cm^ 2 / W, the ceramic copper-clad laminate has a solder layer between the ceramic substrate and the copper layer, the total thickness of the solder layer is 3um-15um, preferably 5-10um, more preferably 7-9um; the solder layer includes a TiN layer and a transition alloy layer, the thickness of the TiN layer is 0.05μm-5μm, preferably 0.5μm-2μm, more preferably 0.07-1.2um. The thickness of the TiN layer accounts for 5%-10% of the total thickness of the solder layer, preferably 5%-8%, more preferably 5%-7%, and the continuous and dense TiN reaction layer can make the copper-clad laminate have a higher peel strength

[0069] The thickness of the transition alloying layer is 2.95μm-10μm, preferably 4-8um, and more preferably 5-8um. The transition alloying layer contains TiSi and TiCu intermetallic compounds and copper-based solid solution. The thickness of the discontinuous layer of TiSi and TiCu intermetallic compounds accounts for 30%-50% of the total thickness of the welding layer, preferably 30%-40%, and more preferably 30-35%, wherein the TiCu phase is embedded and distributed in the TiSi phase; the thickness of the copper-based solid solution accounts for 50%-70% of the total thickness of the welding layer, preferably 55%-70%, and more preferably 55%-65%. Therefore, in the proportion of each component in the welding layer, the copper-based solid solution>TiSi and TiCu phase discontinuous layer>TiN continuous layer, which reduces the influence of the lattice mismatch on the thermal conductivity of the welding layer in the related art where the proportion of the intermetallic compound phase is large and the dispersed heterogeneous interface; wherein the copper-based solid solution accounts for ≥85% by weight of the Cu element in the distribution area, preferably ≥88%, and more preferably ≥90%, and the area presents a color similar to that of the copper layer under a scanning electron microscope. TiSi and TiCu intermetallic compounds are discontinuously distributed, which can buffer thermal stress and improve the reliability of ceramic copper clad boards; the copper-based solid solution has high electrical conductivity, which can improve the thermal conductivity of the solder layer and reduce the thermal resistance of the ceramic copper clad boards.

[0070] It should be noted that the preparation method of the above-mentioned solder paste can refer to some or all of the steps in the above-mentioned preparation method, and the relevant parameters of the above-mentioned metal compounds and adhesives can refer to some or all of the technical features in the above-mentioned embodiments. The parts not described in the solder paste embodiment can also refer to the above-mentioned embodiments and related drawings, and will not be repeated here.

[0071] The scheme of the present application is described below by specific examples. It should be noted that the following examples are only used to illustrate the present application and should not be considered as limiting the scope of the present application. If no specific technology or conditions are specified in the examples, the technology or conditions described in the literature in this area or the product instructions are used. The reagents or instruments used are not specified by the manufacturer, and are all conventional products that can be obtained commercially.

[0072] Example 1

[0073] 1. Preparation of the binder: First, nitrogen was introduced into the reactor, and the nitrogen was introduced three times repeatedly to exhaust the air in the reactor, and then 87.2wt% of pine alcohol was added into the reactor through a glass pipe, and the temperature was slowly raised to 76°C under stirring at a speed of 40rpm; 3% of thickener ethyl cellulose was slowly introduced into the solvent through a pipe, and the mixture was first stirred at a speed of 90rpm for 50min, and then stirred at a speed of 400rpm for 60min; then 9% of dispersant DISPERBYK-168 and 0.5% of surfactant Tween 20 were simultaneously added to the above solution, stirred at a speed of 120rpm, and heated to 200°C for 3h; cooled, filtered using a 120-mesh gauze, 3% of thixotropic agent polyamide wax was added to the filtered substance, and slowly stirred at a speed of 30rpm. After the temperature was raised to 50°C, the speed was adjusted to 900rpm, stirred for 2h, and then slowly cooled, filtered using a 350-mesh gauze to obtain the binder.

[0074] 2. Preparation of metal compounds: Place CuCrZr alloy powder with a conductivity of 83% IACS in a ball mill and mill it at a speed of 150 rpm for 15 minutes in an argon environment; then place Sn alloy powder in a ball mill, first mill it at a speed of 150 rpm for 15 minutes, then mill it at a speed of 1000 rpm for 6 hours, cool it, and use a vibration screening machine to screen it to remove agglomerated particles to obtain an intermediate, which is placed in an argon glove box for storage; titanium hydride and an appropriate amount of process control agent chitosan are placed in a ball mill and milled at a speed of 150 rpm for 15 minutes, then the intermediate and an appropriate amount of process control agent chitosan are placed in a ball mill, milled at a speed of 150 rpm for 15 minutes, and then milled at a speed of 800 rpm for 7 hours. After the ball milling is completed, it will be brought to room temperature and a powdered metal compound with a particle size range of 0.5um-15um will be screened out with a vibration screen.

[0075] 3. Preparation of solder paste: 87wt% [(CuCrZr) 核心层 (Sn) 第一壳层 (TiH 2 ) 第二壳层 The metal compound and 13 wt % of the binder were mixed and stirred by a vacuum planetary disperser, first at a speed of 50 rpm for 1 hour, then at a speed of 250 rpm for 2 hours, and finally at a speed of 360 rpm, a vacuum degree of -99 Kpa, for 1 hour, and filtered evenly, wherein the thickness ratio of the core layer: the first shell layer: the second shell layer of the metal compound was about 6:3.5:1, and the conductivity of the core layer was 83% IACS.

[0076] 4. Screen print the solder paste on one side of the 0.32mm silicon nitride ceramic sheet and dry it at 80℃ for 30min. Then screen print the solder paste on the other side of the ceramic sheet. Repeat the above steps. Cover the surface of the welding layer on both sides with 0.3mm thick oxygen-free pure copper. Place it in a vacuum brazing furnace for degreasing, debinding and sintering. The vacuum degree is 10 -3 Pa, a pressure of 30N, and a temperature of 925°C for 0.5 hour to obtain a ceramic copper-clad laminate, wherein the thickness of the TiN layer in the solder layer of the ceramic copper-clad laminate accounts for 15.5% of the solder layer thickness, and the area of ​​the copper-based solid solution in the solder layer in the transition alloying layer is 58.6%.

[0077] Example 2

[0078] This embodiment provides a solder paste and a ceramic copper-clad laminate, and the preparation method thereof is substantially the same as that of Embodiment 1, except that, in the preparation of the metal compound, CuSiP alloy powder with a conductivity of 89% IACS, SnNi alloy powder and titanium hydride are used to prepare the metal compound [(CuSiP) 核心层 (0.9Sn0.1Ni) 第一壳层 (TiH 2 ) 第二壳层 ].

[0079] Example 3

[0080] This embodiment provides a solder paste and a ceramic copper-clad laminate, and the preparation method thereof is substantially the same as that of Embodiment 1, except that, in the preparation of the metal compound, CuNiSi alloy powder, Sn alloy powder and titanium having a conductivity of 92% IACS are used to prepare the metal compound [(CuNiSi) 核心层 (Sn) 第一壳层 (Ti) 第二壳层 ].

[0081] Comparative Example 1

[0082] This embodiment provides a solder paste and a ceramic copper-clad laminate, and the preparation method thereof is substantially the same as that of Embodiment 1, except that, in the preparation of the metal compound, CuCrZr alloy powder with a conductivity of 70% IACS, Sn alloy powder and titanium hydride are used to prepare the metal compound [(CuCrZr) 核心层 (Sn) 第一壳层 (TiH 2 ) 第二壳层 ].

[0083] Comparative Example 2

[0084] This embodiment provides a solder paste and a ceramic copper-clad laminate, and the preparation method thereof is substantially the same as that of Embodiment 1, except that, in the preparation of the metal compound, CuSiP alloy powder with a conductivity of 60% IACS, SnNi alloy powder and titanium hydride are used to prepare the metal compound [(CuSiP) 核心层 (0.9Sn0.1Ni) 第一壳层 (TiH 2 ) 第二壳层 ].

[0085] Comparative Example 3

[0086] This embodiment provides a solder paste and a ceramic copper-clad laminate, and the preparation method thereof is substantially the same as that of Embodiment 1, except that in the preparation of the metal compound, CuNiSi alloy powder, Sn alloy powder and titanium with a conductivity of 65% IACS are used to prepare the metal compound [(CuSiP) 核心层 (0.9Sn0.1Ni) 第一壳层 (TiH 2 ) 第二壳层 ].

[0087] Test method: ultrasonic scanning test, peel strength test, hot and cold shock test, thermal resistance test, average change rate, and solder layer structure confirmation are performed on the ceramic copper clad laminate.

[0088] Solder paste viscosity test: The viscosity of the adhesives of each embodiment and comparative example was tested at 25±2° C. using a viscometer of model XDV2THA at a rotation speed of 60 rpm.

[0089] Among them, the defective hole rate of the ceramic copper clad laminate after welding adopts the method in GB / T39240-2020 General Principles of Nondestructive Testing and Ultrasonic Testing, and is obtained by calculating the proportion of products with defective holes;

[0090] The peel strength of the ceramic copper clad laminate is tested using the GB / T 11363-2008 brazing joint strength test method;

[0091] The hot and cold shock test is to use a hot and cold shock chamber to test the hot and cold tolerance in the temperature range of -55℃~150℃, where -55℃ and 150℃ stay for 30 minutes respectively, and switch for 15 seconds in between. The peel strength and thermal resistance of 0 and 1000 hot and cold shocks are tested;

[0092] The thermal resistance test is carried out with reference to the ASTM D5470 standard. The sample size is 2.7cm*2.7cm for copper surface and 2.8cm*2.8cm for ceramic. The solder layer structure can be confirmed by SEM / EDX. Specifically, the analysis is set to 1000 times the magnification and 15kV acceleration voltage, and the solder layer is subjected to SEM / EDS analysis.

[0093] Average change rate = (TC1000 times - TC0 times) / TC0 times, applicable to calculation of change rate of peel strength and thermal resistance. TC is the above-mentioned hot and cold tolerance test conducted in the temperature range of -55℃ to 150℃.

[0094] Solder layer structure test: Use SEM to perform linear scanning on the sample in accordance with JY / T 0584-2020 General Rules for Scanning Electron Microscope Analysis Methods.

[0095] Through the line scan function in the SEM, line scans are performed every 2um in the viewing area along the direction perpendicular to the ceramic welding surface. The phase composition is determined according to the content of each element at each point in the line scan position, and then the component area S is calculated based on the distance between adjacent points containing the same phase component along the line scan direction and perpendicular to the line scan direction for the confirmed phase component content in the adjacent multiple line scan paths. a , and then calculate the proportion of the total area of ​​the solder layer a% = (S a / S 总 )*100, where a=TiN, TiSi (including TiCu), copper-based solid solution. The copper-based solid solution area has a Cu element weight ratio of >85% in the distribution area. This area shows a color similar to the copper layer under a scanning electron microscope. The TiN thickness is determined by judging the TiN distribution based on the midpoint position of the line scan extending from the ceramic to the copper layer and the Ti and N element content. Solder layer area S 总 The Ti content along the ceramic side in the line scanning direction is about 0%, and the Cu content along the copper direction is stable and unchanged. Five random areas of the cross section are selected and the S ai (i=1、2、3、4、5), S 总j (j = 1, 2, 3, 4, 5), and then take the average value as a k % = (S ai / S 总j )(i, j, K = 1, 2, 3, 4, 5), and obtain the proportion of each phase in the welding layer.

[0096] from Figure 3 It can be seen that Figure 3 This is the cross-sectional SEM of the welding layer between ceramic and copper in Example 1. The number of voids is 0. The left side is silicon nitride ceramic, the right side is copper, and the middle is the welding layer. The thickness of the welding layer is about 7.56 μm, of which the thickness of TiN is about 0.725 μm.

[0097] The test results are shown in Table 1 below:

[0098] Table 1

[0099]

[0100]

[0101] By comparing Example 1 with Comparative Example 1, Comparative Example 2 with Comparative Example 2, and Comparative Example 3 with Comparative Example 3, it can be seen that the conductivity of the core layer of the metal compound of Examples 1, 2, and 3 is 83% IACS, 89% IACS, and 92% IACS, respectively, and the conductivity of the core layer in Comparative Examples 1, 2, and 3 is 70% IACS, 60% IACS, and 65% IACS, respectively. The experimental results in Table 1 show that the average change rate of the thermal resistance and peel strength of the ceramic copper clad laminates corresponding to Examples 1, 2, and 3 is small; the average change rate of the thermal resistance and peel strength of the ceramic copper clad laminates of Comparative Examples 1, 2, and 3 is large, that is, compared with Comparative Examples 1, 2, and 3, the conductivity of the core layer of Examples 1, 2, and 3 is greater than or equal to 80% IACS solder paste, and the reliability and peel strength of the ceramic copper clad laminates made thereof are greatly improved.

[0102] In addition, by comparing Example 1 with Comparative Example 1, Comparative Example 2 with Comparative Example 2, and Comparative Example 3 with Comparative Example 3, it can be seen that the solder paste made from metal compounds with a core layer conductivity greater than 80% IACS has a lower viscosity, which makes the solder paste have better fluidity.

[0103] In summary, the ceramic copper clad laminate prepared by the solder paste has a low thermal resistance, and improves the plasticity of the solder layer, improves the tolerance of the ceramic copper clad laminate to cyclic thermal stress, can improve the hardness of the ceramic copper clad laminate and the hardness of the solder layer, so that the ceramic copper clad laminate has a higher peel strength.

[0104] Unless otherwise specified, all scientific and technological terms used in this application have the same meaning as those commonly understood by those skilled in the art to which this application belongs. All patents and publications related to this application are incorporated herein by reference in their entirety. The term "comprising" or "including" is an open expression, i.e., including the content specified in this application, but does not exclude the content of other aspects.

[0105] The embodiments of the present application have been described above, and the above description is exemplary, not exhaustive, and is not limited to the disclosed embodiments. Many modifications and changes will be apparent to those of ordinary skill in the art without departing from the scope and spirit of the described embodiments. The selection of terms used herein is intended to best explain the principles of the embodiments, practical applications, or improvements to the technology in the market, or to enable other persons of ordinary skill in the art to understand the embodiments disclosed herein.

[0106] Although the embodiments of the present application have been shown and described above, it can be understood that the above embodiments are exemplary and cannot be understood as limitations on the present application. Ordinary technicians in this field can change, modify, replace and modify the above embodiments within the scope of the present application.

Claims

1. A solder paste, characterized in that: The metal compound includes a core layer, a first shell layer and a second shell layer, wherein the first shell layer wraps the core layer, and the second shell layer wraps the first shell layer; The electrical conductivity of the core layer is greater than or equal to 80% IACS.

2. The solder paste according to claim 1, characterized in that The thickness ratio of the core layer, the first shell layer and the second shell layer is (2-15):(1-9):(0.5-5).

3. The solder paste according to claim 1, characterized in that The invention also comprises a binder, which comprises 75-98 wt % of a solvent, 0.1-20 wt % of a dispersant, 0.05-15 wt % of a thickener, 0.05-0.1 wt % of a surfactant and 0.01-10 wt % of a thixotropic agent.

4. The solder paste according to claim 3, characterized in that The solvent includes one or more of terpineol, tributyl citrate, diethylene glycol butyl ether and diethylene glycol butyl ether acetate; and / or, the dispersant comprises one or more of DISPERBYK-168, stearic acid, polyethylene glycol 200 and polyethylene glycol 400; and / or, the thickener comprises one or more of ethyl cellulose, polyvinyl alcohol and acrylic resin; And / or, the surfactant includes one or more of Tween 20, a silicon-based coupling agent and sodium dodecylbenzene sulfonate; And / or, the thixotropic agent includes one or more of polyamide wax, modified polyurea and hydrogenated castor oil.

5. The solder paste according to claim 3, characterized in that The mass fraction of the metal compound in the solder paste is 70-95wt%, and the mass fraction of the binder is 5-30wt%; The particle size range of the solder paste is 0.5um-50um, and the viscosity range of the solder paste is 20Pas-300Pas.

6. A ceramic copper-clad laminate, characterized in that: The ceramic copper-clad laminate comprises: a solder layer made of the solder paste as described in any one of claims 1-5.

7. The ceramic copper clad laminate according to claim 6, characterized in that: The solder layer comprises a TiN layer and a transition alloy layer, and the thickness ratio of the TiN layer to the transition alloy layer in the solder layer is (0.05-0.1):(0.9-0.95).

8. The ceramic copper clad laminate according to claim 7, characterized in that: The thickness of the TiN layer is 0.05 μm-5 μm, and the thickness of the transition alloy layer is 2.95 μm-10 μm.

9. The ceramic copper clad laminate according to claim 7, characterized in that: The transition alloying layer includes a discontinuous intermetallic compound layer and a copper-based solid solution layer.

10. The ceramic copper clad laminate according to claim 9, characterized in that: The area ratio of the discontinuous intermetallic compound layer and the copper-based solid solution layer in the transition alloying layer is (0.3-0.5):(0.5-0.7).

11. The ceramic copper clad laminate according to claim 9, characterized in that: The discontinuous intermetallic compound layer consists of TiSi and TiCu.

12. The ceramic copper clad laminate according to claim 6, characterized in that: It also includes a ceramic substrate, wherein the thickness of the ceramic substrate is 0.2-2 mm.

13. A method for preparing a ceramic copper-clad laminate, characterized in that: include: providing a ceramic substrate; Solder paste is disposed on both side surfaces of the ceramic substrate to form solder layers on both side surfaces of the ceramic substrate, wherein the solder paste is the solder paste according to any one of claims 1 to 5; A copper sheet is arranged on the surface of the solder paste on one side away from the ceramic substrate, and a brazing process is performed to obtain the ceramic copper-clad laminate.

14. The method according to claim 13, characterized in that The process of setting the solder paste includes screen printing, the screen printing thickness of the screen printing is 6um-20um, the thickness of the solder layer is 3-15um, the brazing process includes vacuum brazing process, the temperature of the vacuum brazing process is 850-1060°C, and the time of the vacuum brazing process is 10min-120min.

Citation Information

Patent Citations

  • Brazing electronic paste, preparation method thereof and application thereof

    CN109648221A

  • Tin-based composite solder based on Cu-Sn-Ag core-shell structure and preparation method and packaging method of tin-based composite solder

    CN116890181A

  • Soldering paste, method for preparing ceramic copper-clad plate and ceramic copper-clad plate

    CN117506235A

  • Active soldering paste composition for ceramic copper coating, ceramic copper coating method and copper-coated ceramic

    CN117510222A

  • Ag-Cu-based active brazing filler metal and production method and application thereof

    CN117532198A

Cited By

  • Solder paste, ceramic copper clad laminate, and method for preparing ceramic copper clad laminate

    WO2026144541A1